Comparison of desflurane and sevoflurane as maintenance inhalational anaesthetic agents for adult patients undergoing neurosurgeries: A systematic review and meta-analysis of randomised trials - Hori Hariyanto; Monika Widiastuti; Carla Oktaviani Pandrya; Kevin Anderson Surya; William Audi (Indian Journal of Anaesthesia)
Background and Aims: Despite its superior blood–gas partition coefficient compared to sevoflurane, use of desflurane in neurosurgery is limited due to concerns about cerebral vasodilation and potential adverse haemodynamic effects. This study aims to systematically evaluate the comparative efficacy and safety of desflurane and sevoflurane in neurosurgical procedures. Methods: A search was performed in the Cochrane Library, Scopus, Europe PMC and Medline databases for articles published until 5 November 2024 using a combination of pertinent keywords. This review includes randomised controlled trials (RCTs) that analyse the comparison between desflurane and sevoflurane in neurosurgery. The risk of bias from each RCT was assessed using the Risk of Bias version 2 tool from Cochrane Collaboration. We utilised random-effects models to evaluate the mean difference (MD) and odds ratio (OR) for the outcomes presented. Results: Fourteen trials, encompassing 904 patients, were included in the analysis. Our analysis revealed significantly faster recovery profiles with desflurane, including reduced emergence time [MD -2.26; 95% confidence interval (CI): -2.99, -1.52, P < 0.00001, I2 = 71%], extubation time (MD -3.02; 95% CI: -3.89, -2.15, P < 0.00001, I2 = 79%) and overall recovery time (MD -3.26; 95% CI: -5.01, -1.51, P = 0.0003, I2 = 83%), compared to sevoflurane. Desflurane was associated with better postoperative cognitive function, as evidenced by higher short orientation memory concentration test scores – a measure of attention and memory – at 15 min (MD: 2.26; 95% CI: 0.13, 4.39, P = 0.04, I2 = 91%) and 60 min (MD: 0.29; 95% CI: 0.09, 0.50, P = 0.005, I2 = 0%) after extubation. We did not find any significant difference in the intra- and/or postoperative events, such as emergence agitation, nausea and vomiting, shivering, hypertension, hypotension, tachycardia, bradycardia, pain and convulsions, between the two groups of intervention. Conclusion: This study suggests that desflurane anaesthesia offers faster recovery with a similar safety profile to sevoflurane for neurosurgery.